2018
DOI: 10.1155/2018/7823182
|View full text |Cite
|
Sign up to set email alerts
|

The EndoBarrier: Duodenal-Jejunal Bypass Liner for Diabetes and Weight Loss

Abstract: The rapid rise of obesity and type 2 diabetes poses a global threat to healthcare and is a major cause of mortality and morbidity. Bariatric surgery has revolutionised the treatment of both these conditions but is invasive and associated with an increased risk of complications. The EndoBarrier is a device placed endoscopically in the duodenum, which is designed to mimic the effects of gastric bypass surgery with the aim of inducing weight loss and improving glycaemic control. This review outlines the current c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 36 publications
1
37
0
4
Order By: Relevance
“…An increase in BA was also seen in patients receiving DJBS, although no changes in anatomy and intestinal transit time are present after the procedure [106]. Other, not yet elucidated mechanisms, must play a role in the alteration of BA in these patients.…”
Section: Bile Acids After Endoscopic Bariatric Proceduresmentioning
confidence: 83%
“…An increase in BA was also seen in patients receiving DJBS, although no changes in anatomy and intestinal transit time are present after the procedure [106]. Other, not yet elucidated mechanisms, must play a role in the alteration of BA in these patients.…”
Section: Bile Acids After Endoscopic Bariatric Proceduresmentioning
confidence: 83%
“…One pig developed an intestinal obstruction because of a DJBL prolapse that spontaneously resolved. Worldwide registry data of 492 patients with DJBL found that the rate of device migration was 3% with an intestinal obstruction of 0.3% of cases ( 20 , 21 ). Central line infection in one pig in our study was not related to either study device.…”
Section: Discussionmentioning
confidence: 99%
“…Endobarrier ® is a 60‐cm fluoropolymer liner that is anchored at the duodenal bulb and covers the enteric mucosal surface till the proximal jejunum and thus it is considered a duodenal‐jejunal bypass liner (DJBL) 38 . For this reason, it does not allow nutrients contact to the mucosa, while pancreatic juice and bile flow down between the liner and the mucosal surface.…”
Section: Duodenal Devicesmentioning
confidence: 99%